Pengaruh Semangat Kerja dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan Pada PT. Multi Media Selular Baturaja - Rosmala Dewi; Dyah Ayu Putriani; Windiara Windiara (Ekonomika, 2022)
Baturaja Mobile Multi Media. The data analysis method used was quantitative method using Multiple Linear Regression analysis tool. The results of the analysis explain that the t-count of each variable of Work Morale (X1) was 2.024 and Work Discipline (X2) was 5.656, which was greater than the t-table value of 2.01973 which stated that all variables had a significant influence on Employees’ Work Productivity at PT. Multi Media Selular Baturaja. Simultaneously, it was found that there was an influence of work spirit and work discipline on the work productivity of PT. Multi Media Selular Baturaja. The calculated F value of 40.975 was greater than the F table of 3.23 which stated that together Work Spirit and Work Discipline had a significant influence on Employees’ Work Productivity at PT. Multi Media Selular Baturaja. The value of the coefficient of determination (R2) of 0.667 means that in this case the contribution of the influence of Work Spirit and Work Discipline on Employees’ Work Productivity was 66.7% while the remaining 33.3% was influenced by other variables outside the variables included in this research model, namely supervision. , calmness, and perseverance in work (Busro, 2020:356).